CODE, COMMIT, CONFIRM: EXPLORING TDD WITH CONTINUOUS INTEGRATION - kumar Gayakwad, Santosh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
When a software product is composed of hundreds of components with complicated dependency relationship among them, change in one component can affect lots of other components' behaviour. Test Driven Development (TDD) is an approach for developing programs incrementally by first writing tests and then writing enough code to satisfy them. Continuous integration is a process that provides rapid and automatic feedback on the security of the applications that are undergoing development. Test-driven development (TDD) and continuous integration (CI) has changed the way software is tested. Software testing was often a separate process at the end of a project. It is now being worked on during the entire development period. TDD and CI rely on unit tests. This paper provides a literature study on two closely related software development approaches viz. Test Driven Development and Continuous Integration.